PRACTICE OF IMPROVING THE FINANCIAL PROVISION FOR HIGHER PROFESSIONAL EDUCATION UNDER REFORMING HIGHER EDUCATION IN ASTRAKHAN OBLAST - R. A. Nabiyev; V. V. Zverev (Russian Journal of Economics and Law)
Objective: to determine ways to improve the financial security of higher professional education (hereinafter - HPE) in conditions of its reforming. Methods: statistical, analytical and abstract-logical. Results: basing on the analysis of financial instruments used by institutions to maintain educational services on a high level, the authors proved the greatest prospects of innovative and entrepreneurial activities as a stable way of earning funds; proposed the ways of solving the major problems in the activity of small innovative enterprises at universities. Scientific novelty: scientifically justified measures to increase the efficiency of activity of small innovative enterprises by improving the innovation infrastructure of the region. Practical value: proposals are elaborated on the improvement of innovation infrastructure of small innovative enterprises on the basis of creation of the Association of small innovative enterprises at the Federal Agency for science and innovations, Ministry of Education and Science of the Russian Federation, directed on the coordination of certain small innovative enterprises and allowing to achieve a synergetic effect.